Rapid Colorimetric Detection of Hg (II) Based on Hg (II)-Induced Suppressed Enzyme-Like Reduction of 4-Nitrophenol by Au@ZnO/Fe3O4 in a Cosmetic Skin Product - Oratile Semong; Bareki Shima Batlokwa (Nanomaterials and Nanotechnology)
Herein, we synthesized gold-coated ZnO/Fe3O4 nanocomposites. Initially, we prepared Fe3O4 magnetic nanoparticles based on the co-precipitation of Fe3+ and Fe2+ under aqueous ammonia as a precipitating agent. Thereafter, the ZnO/Fe3O4 composite was prepared by dispersing the synthesized magnetic nanoparticles into an alkaline zinc nitrate solution. After calcination of the precipitate, the formed ZnO/Fe3O4 composites were coated with gold nanostructures by dispersing the composites in auric acid/ethylene glycol solution in a water bath. The synthesized Au@ZnO/Fe3O4 hybrid material was able to catalyze the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). We demonstrate that this catalytic activity can be exploited for the detection of Hg2+ ions in a cosmetic product. In the presence of Hg2+ ions, the catalytic activity of Au@ZnO/Fe3O4 was greatly suppressed. This novel finding underlies a straightforward, sensitive, and highly selective detection probe for Hg2+. The material exhibited excellent analytical performance as marked by the very low limit of detection (LOD) of 2.34 nM, which was well below acceptable levels of 4.99 μM for mercury in cosmetics as set by the US Food and Drug Administration (FDA), and within the linear dynamic ranges of 0–10 nM. High recoveries ranging from 96.5 to 100.3% accompanied by excellent selectivities toward Hg2+ over potentially interfering species were obtained.